Evaluating the performance of five global gridded potential evapotranspiration products in hydrological simulation: Application in the upper Han River Basin - Minxin Li; Lei Zou; Jun Xia; Hui Cao; Hairong Zhang; Benjun Jia; Jiarui Yu (Journal of Hydrology: Regional Studies)
Study region: The Baihe River Basin located in the upper Han River, central China. Study focus: Potential evapotranspiration (PET) is commonly utilized as the forcing data for hydrological simulation. The lack of observations for estimating PET usually limits the calculation of evapotranspiration in hydrological models. Fortunately, gridded PET products with high data availability provide a great opportunity for hydrological simulation. This study assessed the accuracy of five gridded PET products against the gauge-based data. The Distributed Time Variant Gain Model (DTVGM) was modified to evaluate the performance of these five PET products in streamflow simulation. Additionally, the effect of different PET inputs on simulated runoff components, evapotranspiration, and soil moisture were investigated. New hydrological insights for the region: The results indicate that there are large discrepancies in spatial-temporal distribution of five PET products. Among selected products, GLEAM-b is most consistent with the gauge-based PET in the study region. For the streamflow simulation, five gridded PET products can achieve good performance with the Nash-Sutcliffe efficiency (NSE) values exceeding 0.75 in the validation period. This finding demonstrates the feasibility of using gridded PET products for streamflow simulation. Moreover, GLEAM-b performs better than other products in streamflow simulation according to the evaluation indicators. For simulated runoff components and water balance components, baseflow and evapotranspiration are more sensitive to different PET inputs.